Strategi Bisnis Berkelanjutan dalam Era Digital: Tantangan dan Peluang - Lina Priliana; Monica Evriliani; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2024)
In the context of an ever-changing digital era, companies are faced with significant challenges and opportunities that impact the way they operate and interact with consumers. This journal explores sustainable business strategies that can be adopted by companies to remain relevant and competitive in dynamic markets. By emphasizing the importance of innovation, technology and social responsibility, this research aims to provide in-depth insight into how businesses can adapt to environmental change and meet consumers' increasingly high expectations for sustainability. Through case study analysis and in-depth interviews with industry leaders, the journal identifies best practices and effective strategies in achieving sustainability goals. Research findings show that the integration of product innovation, use of digital technology, commitment to corporate social responsibility, and collaboration with various stakeholders are the keys to creating long-term value and positive impacts on society.